2009
DOI: 10.1007/s11199-009-9649-x
|View full text |Cite
|
Sign up to set email alerts
|

Participant and Word Gender in Age of Acquisition Effects: The Role of Gender Socialization

Abstract: The age of acquisition (AoA) effect represents the processing advantage for developmentally earlieracquired words. An initial norming study identified early and late AoA words having either a strong female-oriented (e.g., flute) or male-oriented (e.g., cigar) semantic bias. Forty-seven female and 45 male Scottish university students participated in a lexical decision task using 100 early and late AoA female-and male-oriented words. Reaction time data showed significant AoA effects for both females and males ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The two sets of stimuli were matched on visual complexity, familiarity, imageability, name agreement, word length and two measures of word frequency (Table 1). Given the predominance of female participants in the preliminary experiment, we note that AoA effects have been reported to be equivalent across male and female adults (e.g., Sereno and O'Donnell, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…The two sets of stimuli were matched on visual complexity, familiarity, imageability, name agreement, word length and two measures of word frequency (Table 1). Given the predominance of female participants in the preliminary experiment, we note that AoA effects have been reported to be equivalent across male and female adults (e.g., Sereno and O'Donnell, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…While the chief variables affecting the speed of recognizing a word are its length, frequency, and contextual predictability, several other lexical variables are also known to influence processing of words (e.g., Sereno et al, 2009 ; Yao et al, 2013 ). For example, high imageable or early AoA words are facilitated relative to low imageable or late AoA words (e.g., Juhasz and Rayner, 2003 ; Balota et al, 2004 ; Sereno and O'Donnell, 2009 ). In addition, the grammatical class of a word also affects its processing (e.g., Sereno, 1999 ; Palazova et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, however, Brysbaert (2017) demonstrated that the best predictor of objective AOA is rated AOA. Behaviorally, words acquired earlier in life are recognized faster than those acquired later (e.g., Cortese & Khanna, 2007; Johnston & Barry, 2006; Juhasz & Rayner, 2006; Sereno & O’Donnell, 2009).…”
mentioning
confidence: 99%
“…The final dimensions of SIZE and GEND have only been the subject of more recent psycholinguistic investigations (e.g., Sereno & O’Donnell, 2009; Sereno et al, 2009; Yao et al, 2013). SIZE is a measure of magnitude (big, small) expressed in either concrete or abstract terms.…”
mentioning
confidence: 99%